The Evaluation of Serum Tumor Necrosis Factor-Like Weak Inducer of Apoptosis, Interleukin-6, Fetuin-A, Homeostatic Model Assessment-Insulin Resistance, and Insulin Levels in Rheumatoid Arthritis Patients in Clinical Remission - Sinem SAĞ,; Derya GÜZEL,; Mustafa Serdar SAĞ,; İbrahim TEKEOĞLU,; Ayhan KAMANLI,; Kemal NAS,; Songül DOĞANAY, (Archives of Rheumatology, 2019)
Objectives: This study aims to examine the relationship of serum tumor necrosis factor-like weak inducer of apoptosis (sTWEAK) levels with interleukin (IL)-6, tumor necrosis factor-alpha (TNF-α), fetuin-A, insulin, homeostatic model assessment (HOMA)-insulin resistance (IR), and disease activity in patients with rheumatoid arthritis (RA) who are in remission or have low disease activity. Patients and methods: Fifty-four patients with RA (8 males, 46 females; mean age 52 years; range 40 to 64 years) and 34 healthy controls (6 males, 28 females; mean age 53 years; range 41 to 65 years) were included in the study. The sTWEAK, fetuin-A, insulin, lipid profile and IL-6 concentrations were determined. The HOMA-IR levels were calculated using a calculator. Disease activity score 28 was used to assess the disease activity. Results: The erythrocyte sedimentation rate, C-reactive protein, fetuin-A, and IL-6 levels were higher in the RA group than in the control group (p=0.004, 0.001, 0.001, and 0.003, respectively). sTWEAK levels were lower in the RA group than in the control group (p=0.007). There were no differences in the TNF-α, HOMA-IR, insulin, and lipid profile levels of the two groups (p>0.05). sTWEAK had a negative correlation with Body Mass Index and fetuin-A (r=-0.261 and r=-0.287, respectively). Conclusion: We found that RA patients had lower sTWEAK levels and higher fetuin-A levels than the control group subjects. Furthermore, these two molecules were associated with each other. This study demonstrated that in RA patients, even if the disease is controlled with treatment, some molecules associated with an increased metabolic and cardiovascular risk continue to function. Follow-up studies on larger populations are warranted to confirm these findings.